2000
DOI: 10.1108/14666180010382590
|View full text |Cite
|
Sign up to set email alerts
|

Grey literature and library and information studies: a global perspective

Abstract: A lot of studies on grey literature abound in the literature. Most of the studies, however, relate to disciplines other than LlS. This study determines the focus and trends of grey literature publications. Other objectives include determining the proportion of grey literature published that focuses on national, regional and global issues, identifying the various formats of grey literature prevalent in LIS, and the major sources used by information professionals in publishing their grey literature research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…This trend is consistent with developments in similarly interdisciplinary research domains including library and information science [1], the health sciences [2,11], marine and fisheries science [8], economics [22], and transportation studies [26,27]. Based on the consensus definition presented at the beginning of the instrument, 70.9% of respondents indicated that grey literature is currently a ''very important'' source of information for karst researchers, with 14.5% stating that it will be more important in the future.…”
Section: Conclusion and Recommendationssupporting
confidence: 78%
See 1 more Smart Citation
“…This trend is consistent with developments in similarly interdisciplinary research domains including library and information science [1], the health sciences [2,11], marine and fisheries science [8], economics [22], and transportation studies [26,27]. Based on the consensus definition presented at the beginning of the instrument, 70.9% of respondents indicated that grey literature is currently a ''very important'' source of information for karst researchers, with 14.5% stating that it will be more important in the future.…”
Section: Conclusion and Recommendationssupporting
confidence: 78%
“…As research into the potential of karst for benefit or hazard to humanity intensifies, information integration and linkages promoting collaboration and connectivity among scientists, decision-makers, educators, and the general public are essential. Karst researchers are faced with three inextricably related challenges: (1) discovering and evaluating relevant information sources, (2) obtaining and preserving ''grey'' karst information sources, and (3) providing interdisciplinary linkages among karst scientists to bring about knowledge discovery and communication. In order to construct a portal that contained information and services most useful to karst researchers, a needs assessment was performed.…”
Section: The Contextmentioning
confidence: 99%
“…While conference proceedings did not play a prevalent role in our study, there is evidence that this venue has the potential to be a vital component of scholarly communication [18], with Ania proposing that "proceedings…provide the medium for reporting [grey literature]" [19]. Pelzer and Wiese's bibliometric study of veterinary literature reported that 50.1% of grey literature citations fell in the conference category [15], which was much higher than the frequency of conference proceedings citations in peer-reviewed nursing journals that was found in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Work that is not published in academic journals or indexed in databases is often given the term 'grey literature' 24 . This large volume of literature includes poster presentations, dissertations, newsletters, census data, government leaflets, corporate documents and committee reports.…”
Section: Source Typesmentioning
confidence: 99%